Factor Analysis Affecting The Level Of Public Knowledge About Dentures Made By Dental Workers - Deto, Mazia Kamalia; Ardlina, Nira (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Tooth loss can impact physical conditions such as aesthetic appearance, mastication, and speech, affecting overall health. Missing teeth can be replaced with dentures. The number of cases indicates that Indonesians still often seek denture treatment from dental workers. This study aimed to identify the factors that affecting the level of public knowledge about dentures made by dental workers. Method: A sample of 107 respondents aged 45-65 years from Kendal Regency, including Brangsong, Boja, Limbangan, Plantungan, Patean, and Sukorejo Districts, was selected using probability sampling with Cochran's formula for cluster random sampling. Data were collected using a questionnaire and analyzed using bivariate analysis, specifically Spearman's correlation and Lambda's correlation tests.Result: The study found that 60% of respondents had good knowledge of dentures made by dental workers, 21% had moderate knowledge, and 19% had low knowledge. Conclusion: Most respondents were aged 45-55 years (36%), had a college education (40%), were unemployed or housewives (41%), and were influenced by environmental and socio-cultural factors (50%). The analysis showed that age (p=0.428) and occupation (p=0.070) did not have a significant effect on knowledge levels, while education level (p=0.000) and socio-cultural environment (p=0.009) did have significant effects.